Quality in Social Work Services: Global Standards, Key Indicators, and Policy Implications - Durmus Senyapar, Hafize Nurgul (Technium Social Sciences Journal, 2025)
Importance and Aims: Quality assurance in social work has become an increasingly critical concern for both scholars and practitioners, as services face growing demands for accountability, effectiveness, and equity. Despite the proliferation of quality frameworks worldwide, there is no universally accepted system for measuring quality in social work, creating inconsistencies in evaluation and practice. This study aims to conceptualize social work quality more comprehensively and to examine how international frameworks, accreditation standards, and methodological tools can be synthesized into a structured model for assessing and improving service excellence. Methods: The study employs a literature-based, exploratory qualitative design, drawing on academic sources, institutional guidelines, and international standards from organizations such as the IFSW, CSWE, EQUASS, and WHO. The analysis covers literature from 2000 to 2025, using thematic synthesis to identify recurring dimensions, indicators, and best practices. Inclusion criteria focused on peer-reviewed, English-language studies addressing social work quality frameworks, accreditation, or performance evaluation. Key Findings: The findings confirm that effectiveness, efficiency, equity, responsiveness, and professionalism remain the core dimensions of quality in social work. However, the study highlights persistent challenges, including the absence of universally agreed benchmarks and the tension between global standards and local adaptation. While international models such as ISO, EQUASS, COA/NASW, and WHO guidelines provide valuable baselines, they often require contextual flexibility to reflect diverse cultural, socio-economic, and institutional settings. Proposed methodologies—including client satisfaction surveys, case resolution rates, Social Return on Investment (SROI), and AI-driven assessment tools—offer valuable insights but must be integrated in hybrid ways to capture both measurable outputs and nuanced client experiences. Practical Implications: This study demonstrates that quality measurement in social work is not only a technical process but also a critical mechanism for advancing social justice, ethical integrity, and inclusive development. The proposed framework supports policymakers in designing evidence-based quality assurance systems, assists practitioners in embedding continuous improvement strategies, and guides organizations in aligning with the Sustainable Development Goals (SDGs) 10, 16, and 17. By emphasizing hybrid methodologies and interdisciplinary collaboration, the study underscores that advancing quality in social work requires moving beyond compliance toward a dynamic process of service excellence, equity, and accountability across diverse contexts.